A SYSTEMATIC LITERATURE REVIEW: BIG DATA IN SMART CITY DEVELOPMENT - Hendi Sama; Tasya Selvia Ulfa; Andik Yulianto (LPPM Nusa Mandiri, 2026)
The modernization of information technology has generated a large volume of data known as Big Data, which plays an essential role in supporting data-driven decision-making. With regard to Smart City development, Big Data contributes to enhancing the effective, efficient, and environmentally friendly public services. However, the utilization of Big Data in Indonesia still faces several challenges, including insufficient supporting infrastructure, limited technical expertise, and issues related to data security and privacy. This study aims to analyze the role of Big Data in Smart City development, identify the most frequently used technologies, and examine the challenges in implementing Big Data within Smart City initiatives. This study adopts the Systematic Literature Review (SLR) approach, following a structured study selection process, 40 articles were initially retrieved and evaluated, with 25 studies ultimately satisfying the methodological criteria for inclusion in the final synthesis. The results of the analysis indicate that Cloud Computing, Big Data, Artificial Intelligence (AI) and Internet of Things (IoT) are the most dominant technological components in Smart City implementation. Furthermore, the study emphasizes that the success of Smart City initiatives is contingent not merely upon technological progress but also on human resource readiness, data quality, and information protection. This research contributes to providing a strategic foundation for policy development and implementation planning of Smart Cities in Indonesia, particularly in strengthening data governance and national digital capacity building to support sustainable urban innovation.